The Influence of Parental Involvement in Educational Management on The Academic Achievement of Students at SMA IT Al-Izzah - Thamrin, Putri Aulia; Putri, Aisyah Guffron Liana; Nugroho, Moch. Nur Syawalludin; Mutmainna (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
Determining the impact, approaches, and procedures for developing, implementing, and assessing programs that can improve students' academic achievement is the purpose of this study, which is to study the relationship between parental involvement in education management and academic achievement. SMAIT Peradaban Al-Izzah in Sorong City is the objective. This study used a qualitative method based on observation of theoretical relationships. Data collection methods include observation, documentation, and interviews. Positive outcomes of parental participation include higher student achievement due to parental awareness, which considers that parents should support the teachers at school in their efforts to educate their children. As parents are considered to be the ones who know their children best, their efforts to inspire a love of learning in their children through motivational support affect their academic performance. In education management, the responsibilities of the school committee include fostering communication between the community and the school and providing ideas, support, and supervision. Schools can continue to improve academic achievement by collaborating effectively to develop programs that better suit students' needs. To achieve the overarching goal of education, parents must actively participate in their children's education, and all parties in the school must work well together.